The Token Economy Method in Reducing Off-Task Behavior Among Elementary School Students - Arrumaisyah Daulay, Annisa; Eka Yulita br Tarigan, Devi; Adawiah, Zain; Syahira Sihombing, Filrly (Universitas Islam Indonesia, 2025)
Off-task behavior is described as undesired actions in a classroom learning situation. Therefore, this research aimed to analyze the implementation of a token economy in reducing off-task behavior among elementary school students. The sample consisted of five elementary school teachers based on the location and a descriptive qualitative method was adopted using a case study. Additionally, data collection methods included observation, interviews, and documentation. The data were processed using domain analysis through the stages of reduction, presentation, and conclusion drawing. The research showed that the implementation of token economy effectively reduced off-task behavior among students during the learning process. The implemented token economy comprised positive and negative reinforcement and punishment, as well as rewards and penalties. Moreover, other methods, such as ice-breaking activities, advice, and motivation, were used as additional reinforcements or support in mitigating off-task behavior among students.